Enhancing Collaborative Problem-Solving Skills through a Multimodal Project-Based Pedagogical Model - Yusuf Tri Herlambang Yusuf; Iim Siti Karimah Iim; Yadi Suryadi Yadi; Ardian Arief Ardian (UIN Siber Syekh Nurjati Cirebon, 2026)
This research is motivated by the low level of Collaborative Problem Solving skills among elementary school students, which encompass problem-solving and collaboration as key requirements for 21st-century learning. This study aims to analyze the effectiveness of a Project-Based Learning model based on a multimodal approach in improving fifth-grade elementary school students' CPS skills. This study used a quantitative approach with a quasi-experimental nonequivalent control group design. The sample size was 57 students: 28 in the experimental group and 29 in the control group. Data were collected through observation and performance assessment based on the OECD CPS framework (2017). Data were analyzed descriptively and inferentially using the Mann-Whitney U test. The results showed a significant improvement in students' CPS skills in the experimental group, with the average score increasing from 37.74 to 89.21, while the control group's score increased from 38.09 to 66.81. The Mann-Whitney test showed a significant difference between the two groups in the posttest (p < 0.001). Furthermore, the performance assessment results also demonstrated superiority of the experimental group over the control group in terms of problem understanding, idea development, collaboration, innovation, and communication of results. This model is able to simultaneously integrate cognitive and social skill development, thus contributing to improving the quality of learning and being relevant for application in the context of 21st-century education.